ACTUAL PROBLEMS OF DEVELOPMENT OF ARTISTIC AND AESTHETIC COMPETENCE OF PRESCHOOL CHILDREN (Innovative Technologica: Methodical Research Journal, 2023)
In the article, the organizational-functional structure of the development of artistic-aesthetic ability in preschool children was clarified on the basis of components (motivational, cognitive, activity-related, motivational in real conditions, and educational-cognitive). Pedagogical-psychological features of the development of artistic-aesthetic ability are determined through gender pedagogical elements (serving to arouse interest in socio-cultural traditions, dialogic attitude, alternative and compatibility with rhythmic movements).